China’s Energy Transition Policy Expectation and Its CO2 Emission Reduction Effect Assessment - Wang, Di; Liu, Xue; Yang, Xiaodi; Zhang, Zhiyuan; Wen, Xinchen; Zhao, Yueying (Frontiers in Energy Research, 2021)
Measuring the expected impact of China's energy transition on carbon dioxide (CO2) mitigation and identifying the key influencing factors in different economic sectors will help to provide better policy recommendations for China's energy transition. According to the previous research results, this paper uses the difference-in-difference (DID) model to pre-assess the CO2 mitigation effect of China's energy transition policy by 2030. The results reveal that the energy transition policy will contribute to the realization of China's expected target of CO2 emission intensity reduction in 2030, but considering the inertia development trend of CO2 emission, the government should pay attention to the orderly promotion of the implementation of energy transition policy in the future. The CO2 mitigation effect of energy transition has significant sectorial heterogeneity, which has positive mitigation effect on industrial sector, but has no obvious impact on transportation, warehousing and postal industry. It is suggested that China should implement sector-differentiated CO2 mitigation strategy, focus on improving the energy efficiency of industrial sector, and promote the clean low-carbon transition of energy consumption structure in construction, transportation, storage and postal industries.